An Algorithm Combining the Branch-Cut Method and Rhombus Phase Unwrapping Algorithm. (September 2020) - Jiang, Han; Xu, Yuanping; Zhang, Chaolong; Xu, Zhijie; Huang, Jian; Tan, Hailong; Lu, Jun
Abstract: In order to solve the problem that the wrapped phase cannot be unwrapped effectively, this paper proposes an algorithm combining the branch-cut method and rhombus phase unwrapping algorithm for unwrap phase. The algorithm combines the advantages of the two methods, at first, the Goldstein's branch-cut method is used to find the residual points in the wrapping phase, then the rhombus phase unwrapping algorithm is used to unwrap the non-residual area phase, finally the phase of the residual area is obtained by using the cubic spline interpolation method, so as to ensure that the phase of each pixel can be unwrapped smoothly. The simulation results verify the feasibility and effectiveness of the algorithm, the combined phase unwrapping algorithm can effectively reduce the line and island phenomenon.